A genetically engineered Escherichia coli that senses and degrades tetracycline antibiotic residue - Zepeng Mu; Zhuoning Zou; Ye Yang; Wenbo Wang; Yue Xu; Jianyi Huang; Ruiling Cai; Ye Liu; Yajin Mo; Boyi Wang; Yiqun Dang; Yongming Li; et al. (Synthetic and Systems Biotechnology, 2018)
Due to the abuse of antibiotics, antibiotic residues can be detected in both natural environment and various industrial products, posing threat to the environment and human health. Here we describe the design and implementation of an engineered Escherichia coli capable of degrading tetracycline (Tc)-one of the commonly used antibiotics once on humans and now on poultry, cattle and fisheries. A Tc-degrading enzyme, TetX, from the obligate anaerobe Bacteroides fragilis was cloned and recombinantly expressed in E. coli and fully characterized, including its Km and kcat value. We quantitatively evaluated its activity both in vitro and in vivo by UV–Vis spectrometer and LC-MS. Moreover, we used a tetracycline inducible amplification circuit including T7 RNA polymerase and its specific promoter PT7 to enhance the expression level of TetX, and studied the dose-response of TetX under different inducer concentrations. Since the deployment of genetically modified organisms (GMOs) outside laboratory brings about safety concerns, it is necessary to explore the possibility of integrating a kill-switch. Toxin-Antitoxin (TA) systems were used to construct a mutually dependent host-plasmid platform and biocontainment systems in various academic and industrious situations. We selected nine TA systems from various bacteria strains and measured the toxicity of toxins (T) and the detoxifying activity of cognate antitoxins (A) to validate their potential to be used to build a kill-switch. These results prove the possibility of using engineered microorganisms to tackle antibiotic residues in environment efficiently and safely. Keywords: TetX, Antibiotic residue, Toxin-antitoxin system, Kill-switch